Evaluation of the Healthy of Workers in the Three Cement Factories of Expansion Badoush, New Badoush and Al-Rafidain in Nineveh Governorate - Al-Helaly, Luay; A. H. Rasheed, Aya; F. Qasim, Ayad (Scientific Journal for Faculty of Science-Sirte University, 2023)
The current Study involved an assessment of the health of workers in three cement production plants and a comparison between them, as these factories were: Expansion Cement Factory, New Badoush cement factory and Al-Rafidain cement factory in Nineveh Governorate, as blood samples were collected for a period from the beginning of August to the end of December (2022), Included the study was (100) workers and for a control group (40), as the study aimed to know the effect of the air pollutants of the three cement factories on the workers by measuring (15) variables of different blood components (White blood cell (WBCs), red blood cell (RBCs), packed cell volume (PCV%), hemoglobin (Hb) concentration), platelet count (PLTs)), as well as measuring biochemical variables to evaluate kidney and liver functions, oxidants antioxidants status. It was observed that there was an increase in the number of both WBC and PLTs Among the three cement workers, especially the Badoush cement factory workers, and there was a reduction in the number of RBC, Hb concentration and PCV% in all cement workers relative to the control group, decrease it was more severe on Badoush workers. The results indicated a rise in the concentrations of urea and creatinine among the three cement workers, especially the Badoush cement factory workers, and less so among the Al-Rafidain workers, as well as an increase in the enzymes: CA, AST, ALT and ALP when compared with the control team. It was observed that there was the rise on the state of oxidative stress for the workers in the three factories and it was the highest among the workers in Badoush, Al-Rafidain, and Expansion factories, respectively, as a result of a decrease in the levels of antioxidants and an increase in the levels of oxidants when compared with the control group. In general, the study concluded that there is a clear Impact of cement pollutants on the workers' health in the three selected cement factories in Nineveh Governorate, and it was more affected by these pollutants on the workers of Badoush Cement, Expansion, and then Al-Rafidain, respectively.